Impact of HIV infection and antiretroviral treatment on N-terminal prohormone of brain natriuretic peptide as surrogate of myocardial function. (28th January 2017) - Schuster, Christopher; Binder, Christina; Strassl, Robert; Aichelburg, Maximilian C.; Blackwell, Emma; Pavo, Noemi; Ramharter, Michael; Hülsmann, Martin; Grabmeier-Pfistershammer, Katharina; Rieger, Armin; Goliasch, Georg
Abstract : Objective: Vasoactive cardiovascular hormones such as the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) are produced upon ventricular stretch and play a central role in neurohumoral pathways of the heart regulating cardiovascular remodeling and volume homeostasis. The impact of HIV infection on these neurohumoral pathways of the heart and its potential reversibility by combinations of antiretroviral therapies remain unclear. Methods: We assessed serum levels of NT-proBNP in 219 antiretroviral therapy–naïve HIV-infected patients with a normal cardiac and renal status at treatment initiation and after attainment of viremic control. Results: Before antiretroviral therapy, NT-proBNP as a surrogate of myocardial function displayed a significant correlation with absolute CD4 + cell count ( r  = −0.31; P  < 0.001) as well as with HIV viral load ( r  = 0.26; P  < 0.001). The median levels of NT-proBNP were 80 pg/ml (36–205) in patients with a CD4 + cell count less than 200 cells/μl and 42 pg/ml (20–80; P  < 0.001) with a CD4 + cell count more than 500 cells/μl. After viremic control, no statistical correlation was present. Conclusion: Higher NT-proBNP levels were observed in treatment-naïve patients with low CD4 + cell count and high HIV viral load, indicating a subclinical impact of HIV infection on myocardial function. This association is reversible by the initiation of antiretroviral therapy and subsequent viral suppression.